Maria Gromadzka-Grzegorzewska, Narodziny polskich nauk administracyjnych, Wyd. UW, Warszawa 1985, ss. 168. - Kulesza, Michał; Wyrzykowski, Mirosław (Czasopismo Prawno-Historyczne, 1986)
Recenzja: Maria Gromadzka-Grzegorzewska, Narodziny polskich nauk administracyjnych, Wyd. UW, Warszawa 1985, ss. 168.